Risk of disease transmission from flexible nasoendoscopy during the coronavirus disease 2019 pandemic. Issue 3 (24th March 2021) - Kavanagh, F G; Connolly, C; Farrell, E; Callanan, D; Brinkman, D; Affendi, A; Lang, E; Sheahan, P
Abstract: Background: Concerns have emerged regarding infection transmission during flexible nasoendoscopy. Methods: Information was gathered prospectively on flexible nasoendoscopy procedures performed between March and June 2020. Patients and healthcare workers were followed up to assess for coronavirus disease 2019 development. One-sided 97.5 per cent Poisson confidence intervals were calculated for upper limits of risk where zero events were observed. Results: A total of 286 patients were recruited. The most common indication for flexible nasoendoscopy was investigation of 'red flag' symptoms (67 per cent). Forty-seven patients (16 per cent, 95 per cent confidence interval = 13–21 per cent) had suspicious findings on flexible nasoendoscopy requiring further investigation. Twenty patients (7.1 per cent, 95 per cent confidence interval = 4.4–11 per cent) had new cancer diagnoses. Zero coronavirus disease 2019 infections were recorded in the 273 patients. No. 27 endoscopists (the doctors and nurses who carried out the procedures) were followed up.The risk of developing coronavirus disease 2019 after flexible nasoendoscopy was determined to be 0–1.3 per cent. Conclusion: The risk of coronavirus disease 2019 transmission associated with performing flexible nasoendoscopy in asymptomatic patients, while using appropriate personal protective equipment, is very low. Additional data are required to confirm these findings in the setting of further disease surges.